Environmental factors influencing potential distribution of Schisandra sphenanthera and its accumulation of medicinal components - Shang, Jingjing; Zhao, Qian; Yan, Pengdong; Sun, Mengdi; Sun, Haoxuan; Liang, Huizhen; Zhang, Dezhu; Qian, Zengqiang; Cui, Langjun (Frontiers in Plant Science, 2023)
Schisandrae Sphenantherae Fructus (SSF), the dry ripe fruit of Schisandra sphenanthera Rehd. et Wils., is a traditional Chinese medicine with wide application potential. The quality of SSF indicated by the composition and contents of secondary metabolites is closely related to environmental factors, such as regional climate and soil conditions. The aims of this study were to predict the distribution patterns of potentially suitable areas for S. sphenanthera in China and pinpoint the major environmental factors influencing its accumulation of medicinal components. An optimized maximum entropy model was developed and applied under current and future climate scenarios (SSP1-RCP2.6, SSP3-RCP7, and SSP5-RCP8.5). Results show that the total suitable areas for S. sphenanthera (179.58×10 4 km 2 ) cover 18.71% of China's territory under the current climatic conditions . Poorly, moderately, and highly suitable areas are 119.00×10 4 km 2 , 49.61×10 4 km 2 , and 10.98×10 4 km 2 , respectively. The potentially suitable areas for S. sphenanthera are predicted to shrink and shift westward under the future climatic conditions (2041-2070 and 2071-2100). The areas of low climate impact are located in southern Shaanxi, northwestern Guizhou, southeastern Chongqing, and western Hubei Provinces (or Municipality), which exhibit stable and high suitability under different climate scenarios. The contents of volatile oils, lignans, and polysaccharides in SSF are correlated with various environmental factors. The accumulation of major secondary metabolites is primarily influenced by temperature variation, seasonal precipitation, and annual precipitation. This study depicts the potential distribution of S. sphenanthera in China and its spatial change in the future. Our findings decipher the influence of habitat environment on the geographical distribution and medicinal quality of S. sphenanthera, which could have great implications for natural resource conservation and artificial cultivation.